Physical stability characteristics of sunflower oil-in-water emulsion containing sodium chloride, stabilized by gelatinized bambara groundnut flour. Issue 1 (1st January 2019) - Adeyi, Oladayo; Ikhu-Omoregbe, Daniel I.O.; Jideani, Victoria Adaora
Abstract: The influence of sodium chloride salt (NaCl) concentrations on the physical stability of sunflower oil (SFO)-in-water emulsions (40 w/w% SFO) stabilized by 7 w/w% bambara groundnut flour (BGNF) was investigated. Oil droplet sizes and emulsion microstructure were measured microscopically. Physical stability was studied using an optical analyzer, Turbiscan MA 2000, by observing changes in backscattering flux (%) at 20°C. NaCl significantly affected ( p < 0.05) emulsion stability of BGNF-stabilized emulsion. Increased NaCl in the emulsion increased droplet size and physical instability of BGNF-stabilized emulsions. The results indicated that the stability of BGNF-stabilized emulsion can be controlled and manipulated using NaCl. Emulsion destabilization involving oil droplet agglomeration is prevalent in all the studied SFO-in-water emulsions and emulsion microstructures were significantly affected by the presence of NaCl in gelatinized BGNF matrix.